DC conductivities from non-relativistic scaling geometries with momentum dissipation - S. Cremonini; Hai-Shan Liu; H. Lü; C.N. Pope (Journal of High Energy Physics, 2017)
Abstract We consider a gravitational theory with two Maxwell fields, a dilatonic scalar and spatially dependent axions. Black brane solutions to this theory are Lifshitz-like and violate hyperscaling. Working with electrically charged solutions, we calculate analytically the holographic DC conductivities when both gauge fields are allowed to fluctuate. We discuss some of the subtleties associated with relating the horizon to the boundary data, focusing on the role of Lifshitz asymptotics and the presence of multiple gauge fields. The axionic scalars lead to momentum dissipation in the dual holographic theory. Finally, we examine the behavior of the DC conductivities as a function of temperature, and comment on the cases in which one can obtain a linear resistivity.